Toxicity-guided assessment of disinfection by-products via machine learning and network toxicology - Jie Wang; Zhujun Liu; Ruipeng Lai; Xianyu Song; Yukun Zhang; Shuangliang Zhao; Honglai Liu (Water Research, 2026)

Soil slips of terrace slope triggered by an extreme rainstorm on the Loess Plateau of China - Rongchang Zeng; Guanghui Zhang; Shukun Xing; Ruipeng Zhu; Ziguan Wang (Geomorphology, 2026)

Numerical investigation of thermodynamic cavitation dynamics over a hydrofoil incorporating surface tension and viscous effects - Weixiang Ye; Ruipeng Wang; Hao Liu; Wenkui Ma; Xianwu Luo (Ocean Engineering, 2026)

Multi-compartmental Ni-MOF@C microcapsules for enhanced electrochemical detection of paracetamol and levofloxacin - Ruipeng Hao; Wanyu Xie; Danping Tian; Yifan Wang; Pei Zhang; Zheng Zhao; Xuwen Gao; Chen-zhong Li; Wenbo Lu (Analytica Chimica Acta, 2026)

Robust matching of SAR and optical images based on style consistency learning - Ruipeng Zhao; Penglin Zhang; Zhaoqian Wang; Wenfei Zhang; Yi Wan; Bin Zhang; Yongxiang Yao; Yongjun Zhang (International Journal of Remote Sensing, 2026)

Enhanced mechanical properties of concrete with 3D corrugated auxetic lattices - Yongpeng Lei; Ruipeng Liu; Xinjuan Zhao; Hui Wang (Engineering Structures, 2026)

Compressive behavior of a novel 3D auxetic lattice reinforced ice-based composite: Experiments and modeling - Ruipeng Liu; Yongpeng Lei; Zhu Liu; Tianhui Hao; Hui Wang; Haotian Guo (Cold Regions Science and Technology, 2026)

Effect of Submarine Speed on Its Motion in Internal Solitary Waves - Maolin Wang; Hui Du; Shaodong Wang; Tianyu Zhang; Pu Xuan; Pai Peng; Ruipeng Li; Zhan Wang (Journal of Marine Science and Engineering, 2026)
Although extensive research has been carried out on the load characteristics of fixed submarines in internal solitary waves, there is still insufficient understanding of the effect of submarine speed on its motion in internal solitary waves. A rapid calculation method for the motion response of a submarine (SUBOFF standard model) in internal solitary waves between two layers of fluid is established in this study, where the internal wave flow field is constructed based on the extended Korteweg-de Vries theory, and the load on the submarine is calculated using the Morison equation. The accuracy of the proposed method is verified by comparison with numerical results and experimental data. The results of the motion response of the submarine when encountering internal solitary waves at different speeds show that there is a significant nonlinear relationship between speed and vertical motion amplitude and maximum pitch angle. A critical speed is further found, beyond which the submarine experiences a secondary falling deep after the initial vertical falling deep.

Magnetic field modulation of ferrimagnetic domain ordering for ultrasensitive xylene detection: a mechanistic investigation - Xiaoxue Xu; Jing Cao; Shuangming Wang; Yao Wang; ZhiXu Ye; RuiPeng Song; Zhuoyue Chen (Chemical Engineering Journal, 2026)

A battery-operated atomic emission spectrometer for determining tin and antimony in human blood using hydride generation and an atmospheric pressure glow discharge excitation source - Yunchong Huang; Peichao Zheng; Jinmei Wang; Jialong Li; Ruipeng Li; Lianbo Guo (Analytica Chimica Acta, 2026)

Function and mechanism of monosodium glutamate residue on improving the humification of chicken manure and spent mushroom substrates co-composting - Xing Wang; Zhiqing Duan; Xuejiao Yin; Zhengrong Hu; Jun Chen; Hui Li; Ruipeng Li; Ziru Li; Weiming Sun; Haihua Zhang; Tongao Yang; Yingchao Zhang; et al. (Journal of Environmental Chemical Engineering, 2025)

Emulsion coating: One-pot method preparing the sealable microporous surfaces with antibacterial and antithrombotic properties - Jingze Liu; Yueze Hong; Yao Xiong; Yage Hu; Jiaqi Wang; Yuan Wei; Tong Wang; Haichao Yu; Ruipeng Xue; Li Yang; Gaocan Li; Rifang Luo; et al. (Chemical Engineering Journal, 2025)

Defect-mediated permeation of deep eutectic solvents in cellulose crystals: A combined experimental and molecular dynamics study - Yuanhong Yu; Xianyu Song; Yanglong Wang; RuiPeng Lai; Yuxiang Nie; Wenjun Xiang; Chuxiang Zhou; Shuangliang Zhao; Honglai Liu (Carbohydrate Polymers, 2025)

New insights into heavy metal cadmium-induced liver injury: Prominent role of programmed cell death mechanisms - Ruipeng Wang; Jun Yan; Honglong Zhang; Xingwang Zhu; Danna Xie; Tingting Wang; Xun Li (Toxicology, 2025)

Applications of biosensing in assessing food flavor: advancements, challenges, and prospects - Kunli Xu; Yangfan Guo; Yadong Wang; Zhijie Yang; Haoying Han; Fanyu Meng; Yanbo Wang; Ruipeng Chen; Bei Wang (Food Chemistry, 2025)

Reinforcement mechanism of black tea on the gel properties of preserved egg protein: Metal ion “pore-blocking effect” and EWP denaturation-aggregation-reorganization - Baochang Li; Yishu Wang; Wan Lin; Ruipeng Ma; Bin Xu; Jun Sun (Food Chemistry, 2025)

Separation and purification of pea protein and its application in nanofiber fabrication via electrostatic spinning - Jingya Qian; Ruipeng Feng; Yizhong Zhang; Feng Wang; Zhongyang Ding; Shuhao Huo; Bin Zou; Guoqiang Guan; Ling Xu (Food Bioscience, 2025)

Nickel isotopic variations in Ni–Cu sulfide deposits: from theoretical predictions to natural observations - Zhuang Ma; Shui-Jiong Wang; Wenzhong Wang; Matthew J. Brzozowski; Yun Zhao; Shengchao Xue; Ruipeng Li; Shangguo Su; Jie Yang (Geochimica et Cosmochimica Acta, 2025)

Optimizing removal and control of inclusions/impurities and recovery of valuable elements in metallurgical melts via electric field: toward circular economy and resource efficiency - Wen-zhi Xia; Hai-chuan Wang; Ruipeng Pang; Yun Zhou; Zhi-you Liao; Ting Wu; Baowen He; Guang-da Bao; Zhen Hou; Shao-long Chu; Ping-fan Ren (Chemical Engineering Journal, 2025)

Correction to: Long noncoding RNA XIST inhibition promotes Leydig cell apoptosis by acting as a competing endogenous RNA for microRNA‑145a‑5p that targets SIRT1 in late‑onset hypogonadism - Jing Wang; Yiqiong Yang; Yang Xu; Zhipeng Xu; Xiaozhi Zhao; Ruipeng Jia; Yutian Dai (Cell and Tissue Research, 2025)

Pollen-inspired novel silver/silica composite microsphere capable of synergistic bacteria-killing for bacteria-infected wound treatment - Hong Zhang; Guanyu Wang; Kang Qin; Ruipeng Chen; Wei Pang; Xuekun Bai; Ziming Li; Wengeng Guo; Bin Zheng; Huanying Zhou; Zhixian Gao (Chemical Engineering Journal, 2025)

Fe3O4@Au magnetic SERS nanotags-based vertical flow immunoassay for simultaneous detection of fumonisin B1, aflatoxin B1 and deoxnivalenol - Ruipeng Chen; Jianfeng Wu; Hui Wang; Muhammad Shemyal Nisar; Yongqi Li; Yuxuan Chen; Yu Mao; Xuemei Nan; Fan Zhang; Liang Yang; Xiangfang Tang; Jianwei Xie; et al. (Analytica Chimica Acta, 2025)

Impacts of meteorology and precursor emission change on PM2.5 and O3 and identification of synergistic emission reduction pathway: A case of combined pollution event in Beijing, China - Hanyu Zhang; Wantong Guo; Ruipeng Wang; Xuejun Wang; Wenxing Shan; Zhiliang Yao (Environmental Pollution, 2025)

Electricity transmission and its effects on resource misallocation and environmental consequences in China: An economic analysis - Ruipeng Tan; Jun Li; Feng Wang; Jing Yang (Energy Policy, 2025)

Synthesis of PbCrO4 nanorods-Ti3C2Tx MXene composites: A sensitive photoelectrochemical sensor for the detection of cysteine in human blood serum - Wenbo Lu; Yupeng Wang; Siyu Liu; Wanyu Xie; Ming Wei; Ruipeng Hao (Analytica Chimica Acta, 2025)

Effect of co-fermentation of Rhodotorula mucilaginosa with Saccharomyces cerevisiae on the quality and flavor profile of cider - Shijiao Liu; Ruipeng Wang; Yunong Zhang; Yiwei Dai; Sufang Zhang; Xinping Lin; Chaofan Ji; Huipeng Liang; Yingxi Chen (Food Bioscience, 2025)

Comparative transcriptome reveals lignin biosynthesis being the key molecular pathway regulating oilseed rape growth treated by SiO2 NPs and biochar - Ziming Wang; Ziyue Wang; Zhaodi Zhang; Qiong Lu; Yikun Sheng; Xiangyuan Song; Ruipeng Huo; Juyuan Wang; Sheng Zhai (Journal of Plant Research, 2025)

Study on the establishment of air pollutant and carbon emission inventory and collaborative emission reduction potential of China's coking industry from 2012 to 2022 - Long Cheng; Zhilan Ye; Wei Wei; Kai Wang; Ruipeng Wang; Lu Yang; Shuiyuan Cheng; Chengzhou Zhang (Science of The Total Environment, 2024)

Water-induced surface ordering facilitating the microcutting of ductile metals - Jiong Zhang; Xiaopeng Wang; Lu Ma; Shibo Xi; Jiaming Zhan; Ruipeng Li; Yonghua Du; Junmin Xue; Hao Wang (Journal of Cleaner Production, 2024)

Carotenoid biosynthesis profiling unveils the variance of flower coloration in Tagetes erecta and enhances fruit pigmentation in tomato - Yaqiong Qiu; Ruipeng Wang; Enqi Zhang; Yafang Shang; Guodong Feng; Wenjing Wang; Yilong Ma; Wenbo Bai; Wan Zhang; Zhiqiang Xu; Wei Shi; Xiangli Niu (Plant Science, 2024)

Unlocking the mechanism of work environment on miners’ unsafe behaviors: A meta-analysis and system dynamics - Leyao Wang; Wenhao Chai; Ninghao Sun; Ruipeng Tong (Resources Policy, 2024)

Quantitative assessment of human error of emergency behavior for hazardous chemical spills in chemical parks - Dongdong Wang; Guoliang Yang; Jixiang Han; Yingquan Duo; Xiaofeng Zhou; Ruipeng Tong (Process Safety and Environmental Protection, 2024)

Cyclic behavior of rubber-coated stud-UHPC shear connectors exposed to reversed cyclic loadings - Shaodi Wang; Yuanhai Li; Ruipeng Wang; Yuhong Ma; Guifeng Zhao; Tianjun Zhang; Dawen Guo (Engineering Structures, 2024)

Enhancing deterministic prediction in unidirectional ocean waves using an Artificial Neural Network with exponential linear unit - Zhongying Feng; Zhan Wang; Kun Zheng; Ruipeng Li; Yuxin Zhao; Ye Wang (Ocean Engineering, 2024)

A new scheme of PM2.5 and O3 control strategies with the integration of SOM, GA and WRF-CAMx - Wenjiao Duan; Xiaoqi Wang; Shuiyuan Cheng; Ruipeng Wang (Journal of Environmental Sciences, 2024)

Long noncoding RNA XIST inhibition promotes Leydig cell apoptosis by acting as a competing endogenous RNA for microRNA-145a-5p that targets SIRT1 in late-onset hypogonadism - Jing Wang; Yiqiong Yang; Yang Xu; Zhipeng Xu; Xiaozhi Zhao; Ruipeng Jia; Yutian Dai (Cell and Tissue Research, 2024)

Joint multi-objective optimization based on multitask and multi-fidelity Gaussian processes for flapping foil - Zhangyuan Wang; Yuqi Yan; Xinyu Zeng; Ruipeng Li; Weicheng Cui; Youzhi Liang; Dixia Fan (Ocean Engineering, 2024)

Determining an optimal control strategy for anthropogenic VOC emissions in China based on source emissions and reactivity - Ruipeng Wang; Xiaoqi Wang; Shuiyuan Cheng; Jiaxian Zhu; Xinyu Zhang; Long Cheng; Kai Wang (Journal of Environmental Sciences, 2024)

Reductions of multiple air pollutants from coking industry through technology improvements and their impacts on air quality and health risks in a highly industrialized region of China - Long Cheng; Wei Wei; Shuiyuan Cheng; Chengzhou Zhang; Zhilan Ye; Kai Wang; Ruipeng Wang (Science of The Total Environment, 2024)

Bacteria drive soil multifunctionality while fungi are effective only at low pathogen abundance - Jiyu Jia; Guozhi Hu; Gang Ni; Muxi Xie; Ruipeng Li; Guangzhou Wang; Junling Zhang (Science of The Total Environment, 2024)

Phytotoxic Effects of Different Concentrations of Zinc Species on Lettuce - Xiaona Zhang; Kaiyue Yin; Ruipeng Huo; Ziming Wang; Shuo Fan; Qingping Ma; Liwei Wang; Sheng Zhai; Juyuan Wang (Water, Air, & Soil Pollution, 2023)

Nonlinear and lagged effects of VOCs on SOA and O3 and multi-model validated control strategy for VOC sources - Ruipeng Wang; Wenjiao Duan; Shuiyuan Cheng; Xiaoqi Wang (Science of The Total Environment, 2023)

Bio-barcode assay: A useful technology for ultrasensitive and logic-controlled specific detection in food safety: A review - Yue Hou; Ruipeng Chen; Zhiguang Wang; Ran Lu; Yonghui Wang; Shuyue Ren; Shuang Li; Yu Wang; Tie Han; Shiping Yang; Huanying Zhou; Zhixian Gao (Analytica Chimica Acta, 2023)

Marine mammal morphometrics: 3D modeling and estimation validation - Changqun Zhang; Haojie Zhou; Fredrik Christiansen; Yujiang Hao; Kexiong Wang; Zhangbing Kou; Ruipeng Chen; Jie Min; Randall Davis; Ding Wang (Frontiers in Marine Science, 2023)
Techniques of 3D modeling have earned increasing popularity in scientific studies as they offered unprecedented traits in representing objects. As with all mathematical models, the 3D model will be useful once its accuracy has been validated with direct measurements and the robustness of its predictive capability tested. Although measures of body mass and volume are essential to comprehend the life history of animals, such morphometrics, especially total volume, are challenging to obtain from marine mammals due to their elusive nature, aquatic lifestyle, and large size. In this study, accurate measurements of body volume were directly detected from fresh carcasses of eleven finless porpoises ( Neophocaena asiaeorientalis sunameri ) and used to validate 3D models recreated from the same animals using Blender 3D graphics. Published models using truncated cones or elliptical shapes, based on 3, 5, 8, or 19 measurements of girths or heights & widths along the body, were also applied to porpoises to verify their accuracy. The Blender-generated 3D model produced the most accurate estimates of body volume compared to conventional truncated models, with a mean error of only 2.5% to the direct volume measurements. When photogrammetric images are available, the model can predict the body volumes based on total length alone. Similar accuracy was possible with the elliptical model using 19 height & width measurements (5% increments in total length). However, significant ( p < 0.001) inaccuracy resulted from truncated models with 3, 5, or 8 girth measurements and elliptical models with 3 or 5 height & width measurements, and the accuracy of these models also decreased significantly as the number of measurement sites was reduced. Moreover, Blender 3D models can be extrapolated to animals with images absent, and such predicted volumes were tested to be trustworthy (overall skill = 0.998, r = 0.998, p < 0.01). Therefore, we recommend that researchers use either digital 3D models or elliptical models with 5% increments sectioning the torso to obtain accurate estimates of the body volumes of free-ranging marine mammals.

How do temperature and precipitation drive dengue transmission in nine cities, in Guangdong Province, China: a Bayesian spatio-temporal model analysis - Yi Quan; Yingtao Zhang; Hui Deng; Xing Li; Jianguo Zhao; Jianxiong Hu; Ruipeng Lu; Yihan Li; Qian Zhang; Li Zhang; Zitong Huang; Jiong Wang; et al. (Air Quality, Atmosphere & Health, 2023)

Stimulus-responsive hydrogels: A potent tool for biosensing in food safety - Xiaoxiao Lin; Zhiguang Wang; Xuexia Jia; Ruipeng Chen; Yingkai Qin; Yalan Bian; Wei Sheng; Shuang Li; Zhixian Gao (Trends in Food Science & Technology, 2023)

A priori and a posteriori studies of a novel spray flamelet tabulation methodology considering evaporation effects - Yicun Wang; Ruipeng Cai; Changxiao Shao; Kun Luo; Jianren Fan (Fuel, 2023)

The synergistic effect of the preceding winter Northern Hemisphere annular mode and spring tropical North Atlantic SST on spring extreme cold events in the mid-high latitudes of East Asia - Hao Wang; Fei Zheng; Yina Diao; Jianping Li; Ruipeng Sun; Xinxin Tang; Yue Sun; Fei Li; Yazhou Zhang (Climate Dynamics, 2022)

National emissions inventory and future trends in greenhouse gases and other air pollutants from civil airports in China - Kai Wang; Xiaoqi Wang; Shuiyuan Cheng; Long Cheng; Ruipeng Wang (Environmental Science and Pollution Research, 2022)

AE and Damage Characteristics of Coal with Different Water Soaked Depths Under Uniaxial Compression - Ruipeng Qian; Guorui Feng; Pengfei Wang (Geotechnical and Geological Engineering, 2022)

A Manta Ray Robot with Soft Material Based Flapping Wing - Qimeng Liu; Hao Chen; Zhenhua Wang; Qu He; Linke Chen; Weikun Li; Ruipeng Li; Weicheng Cui (Journal of Marine Science and Engineering, 2022)
Recent research on robotic fish mainly focused on the bionic structure design and realizing the movement with smart materials. Although many robotic fish have been proposed, most of these works were oriented toward shallow water environments and are mostly built with purely rigid structures, limiting the mobility and practical usability of robotic fish. Inspired by the stability of the real manta ray, a manta ray robot design is proposed with soft material made flapping wing based on an open-source ROV (Remotely Operated Vehicle). The flapping wing structure with three different materials mimics the wide pectoral fins of real manta rays, which have bones, muscles, and skin. Furthermore, its modular design makes it easy to install and disassemble. The kinematic and hydrodynamic analysis of the manta ray robot are simulated in this paper. The actual manta ray robot is fabricated and several sets of test are performed in the pool. The robot can swim forward continually and stably with a simple rolling and pitching pattern.

Modeling health impacts of air pollutant emissions from the coal-fired power industry based on LCA and oriented by WTP: a case study - Ruipeng Tong; Yiran Wang; Xu Zhao; Xiaoyi Yang (Environmental Science and Pollution Research, 2022)

Settling velocity of irregularly shaped microplastics under steady and dynamic flow conditions - Zhen Wang; Ming Dou; Pengju Ren; Bin Sun; Ruipeng Jia; Yuze Zhou (Environmental Science and Pollution Research, 2021)

Effectiveness of road dust suppressants: insights from particulate matter-related health damage - Boling Zhang; Yiran Wang; Xu Zhao; Lanxin Cao; Ruipeng Tong (Environmental Geochemistry and Health, 2021)

Monitoring and evaluating the control effect of dust suppressant on heavy metals based on ecological and health risks: a case study of Beijing - Ruipeng Tong; Yingqian Fang; Boling Zhang; Yiran Wang; Xiaoyi Yang (Environmental Science and Pollution Research, 2021)

Abundance and removal characteristics of microplastics at a wastewater treatment plant in Zhengzhou - PengJu Ren; Ming Dou; Cai Wang; GuiQiu Li; Ruipeng Jia (Environmental Science and Pollution Research, 2020)

Modeling Canopy Carbon and Water Fluxes Using a Multilayered Model over a Temperate Meadow in Inner Mongolia - Nina Chen; Anzhi Wang; Juan An; Yushu Zhang; Ruipeng Ji; Qingyu Jia; Ziqi Zhao; Dexin Guan (International Journal of Plant Production, 2020)
To incorporate canopy vertical structure in a process-based model over a temperate meadow, a multilayered model estimated canopy carbon flux ( F c ) and water flux ( LE ) was applied by comparing with eddy covariance measurements in Inner Mongolia, China. Simulations of diurnal, seasonal CO 2 and H 2 O fluxes and model sensitivity to parameters and variables were analyzed. The results showed that the model underestimated F c and LE by about 0.6% and 5.0%, respectively. It was able to simulate the diurnal and seasonal variation of F c and LE and performed well during the day and in the growing season, but poorly at night and early in the growing season. F c was more sensitive to the leaf nitrogen content distribution coefficient and maximum catalytic activity of Rubisco, whereas LE showed greater sensitivity to the stomatal conductance parameter a 1 , empirical coefficient of stomatal response to saturated vapor pressure difference V pds0 , and minimum stomatal conductance of CO 2 g sc0 . The response of F c to environmental factors was ranked as air CO 2 concentration ( C a ) > air temperature ( T a ) > photosynthetically active radiation (PAR) > soil water content ( θ sm ) > vapor pressure deficit (VPD) > wind speed ( u 0 ). The response of LE to environmental factors was ranked as T a > VPD > θ sm > PAR> C a > u 0 . The response of LE to vegetation characteristic parameters was greater than that of F c .

Interaction effects and an optimization study of the microparameters of the flat-joint model using the Plackett-Burman design and response surface methodology - Wei Sun; Shunchuan Wu; Ziqiao Cheng; Liangfeng Xiong; Ruipeng Wang (Arabian Journal of Geosciences, 2020)

Adiponectin inhibits vascular smooth muscle cell calcification induced by beta-glycerophosphate through JAK2/STAT3 signaling pathway - Yan Lu; Yichao Ma; Ruihua Wang; Jing Sun; Beibei Guo; Ruipeng Wei; Yongping Jia (Journal of Biosciences, 2019)

Incidental self-processing modulates the interaction of emotional valence and arousal - Qianfeng Wang; Li Zheng; Lin Li; Xiao Xu; Xuemei Cheng; Ruipeng Ning; Zoltan Dienes; Xiuyan Guo (Experimental Brain Research, 2015)

Molecular characterization of putative biocorroding microbiota with a novel niche detection of Epsilon ‐ and Zetaproteobacteria in Pacific Ocean coastal seawaters - Hongyue Dang; Ruipeng Chen; Lin Wang; Sudong Shao; Lingqing Dai; Ying Ye; Lizhong Guo; Guiqiao Huang; Martin G. Klotz (Environmental Microbiology, 2011)
Summary Submerged metal surfaces in marine waters undergo rapid microbial colonization and biocorrosion, causing huge damage to marine engineering facilities and significant financial losses. In coastal areas, an accelerated and particularly severe form of biocorrosion termed accelerated low water corrosion (ALWC) is widespread globally. While identification of biocorroding microorganisms and the dynamics of their community structures is the key for understanding the processes and mechanisms leading to ALWC, neither one is presently understood. In this study, analysis of constructed clone libraries and qPCR assays targeting group‐specific 16S rRNA or functional marker genes were used to determine the identity and abundance of putative early carbon steel surface‐colonizing and biocorroding microbes in coastal seawater. Diverse microbial groups including 10 bacterial phyla, archaea and algae were found to putatively participate in the surface‐colonizing process. Analysis of the community structure of carbon steel surface microbiota revealed a temporal succession leading to ALWC. By extending the current state of knowledge, our work demonstrates the global importance of Alphaproteobacteria (mainly Rhodobacterales ), Gammaproteobacteria (mainly Alteromonadales and Oceanospirillales ), Bacteroidetes (mainly Flavobacteriales ) and microalgae as the pioneer and sustaining surface colonizers that contribute to initial formation and development of surface biofilms. We also discovered Epsilonproteobacteria and the recently described Zetaproteobacteria as putative corrosion‐causing microorganisms during early steps of the ALWC process. Hence, our study reports that Zetaproteobacteria may be ubiquitous also in non‐hydrothermal coastal seawaters and that ALWC of submerged carbon steel surfaces in coastal waters may involve a highly diverse, complex and dynamic microbial consortium. Our finding that Epsilon ‐ and Zetaproteobacteria may play pivotal roles in ALWC provides a new starting point for future investigation of the ALWC process and mechanism in marine environments. Further studies of Epsilon ‐ and Zetaproteobacteria in particular may thus help with the design of effective corrosion prevention and control strategies.